ANALISIS BENTUK PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA (Studi Di Desa Karae Kecataman Siompu Induk Kabupaten Buton Selatan) - Fitria, Fitria; Yusuf, Muhammad; Muhammad Elwan, La Ode (REZ PUBLICA, 2020)
This study aims to determine the level of community participation in village development and to find out the factors that influence the level of community participation in village development. This type of research uses descriptive qualitative research methods and is supported by primary data sources and secondary data. Data collection techniques with library studies and field studies (observation, interviews, and documentation).in determining the informants of this study using purposive sampling, amounting to 9 people consisting of the village head, village secretary. The results of the study indicate that the form of community participation in development in then Karae village, this can be seen from the 4 dimensions used, namely participation in planning, implementing, monitoring and evaluating, and utilizing the results. But there is a dimension that does not involve the community, namely monitoring, and evaluation. While the factors that influence it are; Include (sex, age, occupation, justice and education ) and external factors (government and LSM institution)